2021
DOI: 10.24953/turkjped.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of micronutrient levels in children and adolescents with obesity and their correlation with the components of metabolic syndrome

Abstract: Background. Obesity is a significant public health problem worldwide. Vitamin deficiencies, developing due to monotype nutrition, are more likely to be observed in patients than healthy children. The present study evaluates vitamin and micronutrient levels in children and adolescents with obesity and metabolic syndrome compared to healthy controls. Methods. The study included 73 patients with obesity, 64 patients with metabolic syndrome and 71 healthy children (control group) aged 10 to 16 years. Physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…This previous meta-analysis indicated that folate does not influence FPG, but improves insulin resistance by decreasing insulin levels. Our results, showing no association between serum folate and FPG levels, are consistent with the findings of this previous meta-analysis by Akbari et al A recent study of children and adolescents revealed significantly decreased folate levels observed in groups with obesity and MetS [38]. Moreover, a recent study of older adults suggested that higher folate intake may be related to a lower MetS score [32].…”
Section: Discussionsupporting
confidence: 93%
“…This previous meta-analysis indicated that folate does not influence FPG, but improves insulin resistance by decreasing insulin levels. Our results, showing no association between serum folate and FPG levels, are consistent with the findings of this previous meta-analysis by Akbari et al A recent study of children and adolescents revealed significantly decreased folate levels observed in groups with obesity and MetS [38]. Moreover, a recent study of older adults suggested that higher folate intake may be related to a lower MetS score [32].…”
Section: Discussionsupporting
confidence: 93%
“…A study reported that the intake of niacin in overweight boys was significantly lower than that of non-overweight boys ( 55 ). Studies had found that long-term use of vitamin B-6 and B-12 supplements is significantly associated with lower levels of weight gain in overweight or obese men and women ( 56 , 57 ). These studies, combined with the findings of B-vitamins status and obesity, strengthen the argument that it may play an important role in adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate impact of obesity may be a feasible research direction. However, much of the literature concerning the relationship between vitamins and obesity was controversial or contradictory [ 78 , 79 ]. Lignan, one kind of phytochemical, is defined as phytoestrogen due to its estrogenic and antiestrogenic properties [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%